Employment Law and Gig Economy Workers: Assessing Legal Protections and Rights - Ali Hassan Al-Obaidi; Zainab Ahmed Al-Mahdi; Hussein Rashid Al-Khafaji (International Forum of Researchers and Lecturers, 2024)
The rise of the gig economy has created a workforce with unique challenges in terms of labor rights and protections. This article examines the implications of employment law for gig economy workers, focusing on rights such as minimum wage, social security, and workplace safety. By analyzing case law and policy frameworks, the study assesses the extent to which current employment laws accommodate the needs of gig workers and proposes legal reforms to address gaps in protection and benefits.